Idk what the hell all that is but x = 1.802775637731995
4x^2 - 13 = 0
4x^2 = 13
13/4=3.25
x^2 = 3.25
x = ~1.8
Answer:
Step-by-step explanation:
because both equations do not have matching numbers for the x or y variable, and both equations are positive you are going to have to multiply each equation by a number so that there will be at least one variable with the same number but with opposite signs.
it does not matter which variable you choose.
lets use y because 2 and 3 are smaller then 2 and 5.
so lets multiply the first equation by 2 in order to get y equal to 6.
2(2x)+2(3y)=(2)6
(do not forget to multiply what the equation is equal to also)
4x+6y=12
now for the second equation we need y to equal negative 6
-3(5x)+-3(2y)=-3(4)
-15x-6y=-12
now lets put the 2 new equations next to each other and see what we can cancel out
4x+6y=12
-15x-6y=-12
-11x=0
x=0
now plug 0 in for x and solve for y (it does not matter which of the 4 equations you choose to solve.
2(0)+3y=6
3y=6
y=2
so your answer is x=0, y=2
You combine the numbers that have the same letter attached to them. Then you add or subtract the bumbers from each other to. After that you make the numbers and the numbers with letters into one equation
Ex: 13+5r+7r= 13+12r
Step-by-step explanation:
2w+w=3w If theres a letter by itself it means theres a 1.
Answer:
C & D
Step-by-step explanation:
x² + 3x - 3 = 0
a = co efficient of x² = 1
b= co efficient of x = 3
c = constant = -3
roots = (-b ±
)/2a
= (-3±
)/2*1
= (-3±
)/2
= (-3±√21)/2
![x = \frac{-3+\sqrt{21}}{2} ; x =\frac{-3-\sqrt{21}}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%2B%5Csqrt%7B21%7D%7D%7B2%7D%20%20%20%20%20%3B%20x%20%3D%5Cfrac%7B-3-%5Csqrt%7B21%7D%7D%7B2%7D)
Answer:
Kya Hua Hai Bhai Sab Kuchh khae Duniya Mein Sab Koi pata nahin to Aap To Pyar Karte